Associations between udder health and reproductive performance in United Kingdom dairy cows - Hudson, C.D.; Bradley, Andrew J.; Breen, J.E.; Green, Martin J. (American Dairy Science Association, 2012)
The objective of this research was to evaluate the relationship between udder health and reproductive performance in UK dairy cows. Data from 80 herds were restructured such that each unit of data represented a 2-d period during lactation where a cow was at risk of becoming pregnant. Multilevel discrete-time survival models were then used within a Bayesian framework to explore associations between reproductive outcomes and a variety of potential explanatory variables. Separate models were constructed using 2 different univariate binary outcomes: a cow becoming pregnant during a risk period and a cow becoming pregnant as a result of a given service. Potential explanatory variables included occurrence of clinical mastitis and a categorical representation of individual cow somatic cell count (SCC), both at a variety of timings relative to the risk period. Posterior predictions were used to assess model fit and to check model building assumptions. These demonstrated that the model represented the data well. Within-sample Monte Carlo simulation (i.e., use of the model to predict outcomes for cases within the data set, repeated over a large number of iterations) was used to illustrate results as posterior predicted relative risks. A negative association was found between reproductive performance and cases of clinical mastitis over a wide time frame relative to the risk period (from 28 d before to 70 d after the risk period). A similar negative association with the probability of a service leading to a pregnancy (pregnancy rate) was observed over the same time frame. Higher SCC recordings (i.e., those more likely to be associated with an intramammary infection) were also associated with decreased reproductive performance, especially where an individual cow SCC of greater than 399,000/mL was recorded in the 30 d following a risk period or service. This research demonstrates that both clinical and subclinical mastitis are associated with a reduction in reproductive performance, and that this influence varies in magnitude but can be exerted over a prolonged period.